장애인 사격선수들을 위한 경기 멘탈플랜 프로그램 적용 - 김영숙; Youngsook Kim; 윤서진; Seojin Youn (Ch'eyuk kwahak yŏn'gu, 2025)
[목적] 본 연구는 장애인 사격선수들이 최적의 심리 상태를 유지하여 최고의 경기력을 발휘할 수 있도록, 선수 맞춤형 멘탈 플랜(Mental Plan) 프로그램을 개발·적용하여 그에 대한 효과성(집중력, 자신감, 긴장풀기)을 검증하는 데 목적이 있다. [방법] 연구 대상은 올림픽에서 메달 획득 경력이 있는 장애인 사격 선수 6명이며, 개방형 설문과 면담을 통해 도출된 주의 집중 요인을 바탕으로 총 6회기 구성의 멘탈플랜 프로그램을 설계·적용하였다. [결과] 첫째, 주의집중 도움 요인은 행위집중, 호흡, 루틴, 신체컨디션 조절, 기타 순으로 분류되었으며, 주의 집중 방해요인은 수행무관사고, 부정적 신체컨디션, 주요타자, 외부환경, 기타 순으로 분류되었다. 다음은 경기 바로 전날 주의집중 요인들을 탐색한 결과 긍정적 사고, 심상, 음식섭취조절, 수면조절, 의복준비, 기타 순으로 분류되었다. 또한, 경기 전 주의집중 요인들을 탐색한 결과 행위심상, 호흡, 시합준비, 집중, 스트레칭, 화장실 사용, 기타 순으로 분류되었으며, 경기 중 주의집중 요인들을 탐색한 결과 긍정적 혼잣말, 루틴, 호흡, 사고정지, 기타 순으로 분류되었다. 둘째, 멘탈플랜 프로그램은 호흡 및 루틴 등 총 6회기로, 회기당 40~50분 소요되도록 구성하였다. 프로그램 적용 전·후 비교 분석 결과 집중력, 자신감, 긴장풀기 능력에서 통계적으로 유의미한 향상이 나타났다. [결론] 본 프로그램은 선수 개별 특성에 기반한 실천적 심리기술훈련의 효과를 입증하였으며, 장애인 사격선수 대상 스포츠 심리지원의 실효성과 적용 가능성을 제시한다는 점에서 의의가 있다. PURPOSE This study aimed to develop and implement a customized mental plan program to facilitate an optimal psychological state and peak performance among para shooting athletes. It also sought to empirically verify this program’s psychological effects by focusing on improvements in concentration, confidence, and relaxation. METHODS A total of six para shooting athletes who had earned medals in the Paralympic Games underwent six program sessions that were designed and implemented based on attention-related psychological factors identified through open-ended surveys and in-depth interviews. RESULTS The athletes’ attention was facilitated by task-focused behavior, breathing control, performance routines, and physical condition management. Meanwhile, their concentration was hindered by task-irrelevant thoughts, negative physical states, and external distractions. These factors were further categorized according to competition phase: the day before, precompetition, and during competition. Based on the statistical analysis, significant improvements were observed in the athletes’ concentration, confidence, and relaxation. CONCLUSIONS The custom program was practically effective as an intervention for psychological skills tailored to experienced para shooting athletes’ individual needs. The findings offer valuable insights for developing strategies supporting the psychological states of athletes in disabled sports.